Neuroprotective effects of curcumin via autophagy induction in 6-hydroxydopamine Parkinson's models. (May 2022) - He, Hai-Jun; Xiong, Xi; Zhou, Shuoting; Zhang, Xing-Ru; Zhao, Xuemiao; Chen, Lingli; Xie, Cheng-Long
Abstract: Curcumin, a polyphenolic compound extracted from curcuma longa, acts as a nontoxic matter with anti-oxidant and anti-inflammatory effects as well as antiproliferative activities. Here, our research aimed to explore the neuroprotective effects of curcumin both in the 6-hydroxydopamine (6-OHDA)-lesioned rat model of Parkinson's disease (PD) in vivo and 6-OHDA-lesioned PC12 cells in vitro. In vitro, 6-OHDA caused a distinct decrease in cell viability of PC12 cells (150 μM). With the incubation of curcumin (1 μM), 6-OHDA-induced apoptosis was suppressed, increasing the autophagy markers (LC3-II/LC3-I, Beclin-1) and inhibiting phosphor-AKT/AKT, phosphor-mTOR/mTOR. In vivo, curcumin (50 mg/kg) reduced the accumulation of a-synuclein and led to higher parkinsonian disability scores in 6-OHDA-lesioned PD rats, contributing to induction of autophagy through inhibiting AKT/mTOR signal pathway. Moreover, treatment with autophagy inhibitors, such as 3-MA and chloroquine, abolished the neuroprotective effects of curcumin as evidence by compromised autophagy and declined motor behavior in PD rats. In conclusion, the present study demonstrated that curcumin repressed PC12 cell death in vitro and improved parkinsonian disability scores in vivo by inhibiting AKT/mTOR signaling pathway which mediated by autophagy, indicating a potential value of curcumin in the therapeutic intervention of Parkinson's disease. Highlights: Curcumin reduced the neurotoxic chemical-induced injury in PC12 cells and improved the parkinsonian disability scores in PD animals models. 3-MA and chloroquine both abolished the neuroprotective effects of curcumin in PD rats. Curcumin repressed PC12 cell death in vitro and improved parkinsonian disability scores in vivo by inhibiting AKT/mTOR signaling pathway.